Thrombin Generation in Preterm Newborns With Intestinal Failure-Associated Liver Disease - Ghirardello, Stefano; Raffaeli, Genny; Scalambrino, Erica; Cortesi, Valeria; Roggero, Paola; Peyvandi, Flora; Mosca, Fabio; Tripodi, Armando (Frontiers in Pediatrics, 2020)
Background and Aim: Intestinal failure-associated liver disease (IFALD) affects one-fifth of neonates receiving parenteral nutrition (PN) for more than 2 weeks. We aimed to define the effect of IFALD on hemostasis of preterm infants. Methods: This is an ancillary analysis of a prospective study aimed at defining coagulation in preterm infants. We included neonates exposed to PN (at least 14 days), in full-enteral feeding. We compared thrombin generation in the presence of thrombomodulin, defined as endogenous thrombin potential-ETP, PT, aPTT between infants with IFALD vs. those without (controls), at birth, and after 30 days. IFALD was defined as conjugated bilirubin ≥1 mg/dl. Results: We enrolled 92 preterm infants (32 IFALD; 60 controls). Cholestatic patients had a lower birthweight, longer exposure to PN, and longer hospitalization. Infants with IFALD showed longer median PT (12.8-vs.-12 sec; p = 0.02) and aPTT (39.2-vs.-36.5 sec; p = 0.04) than controls, with no difference in ETP. Conclusions: Despite prolonged PTs and aPTTs infants with IFALD had similar ETP than those without.